Effectiveness of Information Education and Communication on Knowledge Regarding Suicide and its Prevention among Adolescents in Selected Schools of Panipat (International Journal of Nursing Education, 2020)
Background: Suicide is a problem of both public and mental health and is a leading cause of death especially among adolescents. Considering the high rates in adolescents the importance of providing information education and communication helps in promoting social integration and preventing suicide among adolescents. Aims and Objectives: Study intended to evaluate the effectiveness of information education and communication regarding suicide and its prevention among adolescents in experimental group. Materials and Method: Evaluative research approach was selected and true experimental research design was adopted to evaluate the effectiveness. Total sample size was 60 and in each group 30 samples were recruited through systematic random sampling technique. Structured knowledge questionnaire was developed and data was collected from the samples through self –reporting questionnaire method. The collected data were analysed by means of descriptive and inferential statistics by using SPSS (IBM Version 20). Results: The post - test mean score among samples in experimental group was 17.23 (? = 4.04) and in control group was 9.58 (? = 3.24). Independent ‘t’ test value was 8.0909 for the degree of freedom 58 and it is statistically significant at P value <0.05. Conclusion: Evidence obtained from the current study shows improvements in adolescent’s knowledge and awareness about suicide and its prevention. This programme also increased the problem-solving skills and self-efficacy as well as reductions in self-reported suicide vulnerability.